2009
DOI: 10.1177/0363546508328416
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow-up of Acute Arthroscopic Bankart Repair for Initial Anterior Shoulder Dislocations in Young Athletes

Abstract: At long-term follow-up, acute arthroscopic Bankart repair for first-time traumatic anterior glenohumeral dislocations resulted in excellent subjective function and return to athletics in young, active patients with an acceptable rate of recurrence and reoperation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
124
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(135 citation statements)
references
References 21 publications
(38 reference statements)
6
124
2
3
Order By: Relevance
“…Authors noted that it was too early for a final determination given the scope of purpose of the paper. The same authors published a long-term paper a few years later [57] with a mean follow-up of 140 months, reporting a 37.5 % of complications, with a 15 % of recurrence in dislocations and a 22.5 % of resubluxation. Reintervention rate was 15 % when mean clinical followup was longer.…”
Section: Discussionmentioning
confidence: 99%
“…Authors noted that it was too early for a final determination given the scope of purpose of the paper. The same authors published a long-term paper a few years later [57] with a mean follow-up of 140 months, reporting a 37.5 % of complications, with a 15 % of recurrence in dislocations and a 22.5 % of resubluxation. Reintervention rate was 15 % when mean clinical followup was longer.…”
Section: Discussionmentioning
confidence: 99%
“…However, the repairs in this series were mixed with some patients having a suture anchor repair and some having a repair with tacks which has been shown to be suboptimal compared to suture anchors. Similarly, Owens et al reported a 14 % rate of recurrence following arthroscopic stabilization of fi rst-time dislocation in a series of 40 athletes treated with bioabsorbable tacks [ 106 ]. On the other hand, Burkhart and DeBeer demonstrated that even in contact athletes, an acceptable recurrence rate (6.5 % in their series) can be achieved with a suture anchor-based arthroscopic Bankart repair [ 25 ].…”
Section: Experience In Treatment Of Athletesmentioning
confidence: 99%
“…Bottoni et al (4) found a recurrence rate of 75% among patients who had been treated conservatively and that if arthroscopic suture of the Bankart lesion was performed after the first episode of TAD of the shoulder, the rate found was 11.1%. After this study, treatment for TAD of the shoulder under arthroscopic viewing started to be used (1,4,8,9) . The present study had the aim of evaluating the clinical results obtained among a group of patients who underwent suturing of a Bankart lesion under arthroscopic viewing, after a first episode of TAD of the shoulder.…”
Section: Introductionmentioning
confidence: 99%